Mental health and pandemic: association between stress, work and Covid-19 in medical professionals (Research, Society and Development, 2022)
Objective: to identify the association between stress, aspects related to the Covid-19 pandemic and occupational characteristics in postgraduate doctors in Family Health. Method: a quantitative, descriptive and exploratory study with a non-probabilistic sample of 395 postgraduate doctors in Family Health working in the Mais Médicos Program, carried out between September and November 2020. In the analysis sociodemographic, work and , stress data were compared through the chi-square test, ODDS RATION and multiple logistic regression. Results: it was evidenced that female doctors with 3 years of experience and who did not consider biosecurity measures as sufficient to avoid contagion by Covid-19 had a greater chance of stress, as well as those professionals who had increased work demand, consumed higher doses of alcohol and/or psychotropic drugs and had changes in their body weight. Conclusion: the influence of the pandemic context was observed in the development of physicians' stress associated with changes in the organizational character of health services.